Erosion of an intertidal mussel bed by ice- and wave-action. (1st September 2015) - Donker, J.J.A.; van der Vegt, M.; Hoekstra, P.
Abstract: The persistence of intertidal mussel beds is governed by both biotic and abiotic processes. Many studies have shown that waves and currents are able to erode mussels from an intertidal mussel bed, but here it is demonstrated that in temperate regions ice action can be important as well. These findings result from a 27-month-long monitoring campaign on a mature intertidal mussel bed in the Dutch Wadden Sea. Daily camera observations revealed two periods in which significant erosion occurred. The first event occurred in a period during which the bed was covered by ice. Ice action resulted in an initial decrease of 19% in mussel covered area around the monitoring station. The losses were concentrated in three erosion hotspots of which the largest two were located close to the beds' edge. Around these hotspots, up to 0.3 m high ridges of piled up mussels had formed, with the highest ridges located westward of these erosion gaps. The observed topographic changes support the view that the mechanism by which the bed was damaged was, at least partly, due to physical disturbance by scouring ice. Recovery of mussel cover was limited in the 19 months following the ice action event. Due to sedimentation and reorganization of the mussels, initial relief inside the mussel bed was reduced again and mussels spread out over a larger area. Height differences between uncovered parts and mussel covered parts increased as a result of sedimentation in mussel covered areas. Wave action during a storm period caused a further reduction in mussel cover. Especially areas that were previously elevated by ice action suffered from large losses. Wave erosion occurred during multiple wind events, causing initially small erosion gaps to expand outward and increase in extent. The results suggest a twofold impact of wave and ice action on mussel bed cover: firstly, by directly eroding mussels from mussel beds; secondly, by indirectly increasing the exposure of mussel beds to wave induced bed shear stresses. Abstract : Highlights: Ice action creates topographic changes in intertidal mussel beds. Mussel bed relief is increased by sedimentation in mussel covered areas. High relief at the seaward edge exposes the bed to erosion by wave action. Edges around a wave action erosion gap are vulnerable to erosion. Erosion by wave action can trigger a chain of wave erosion events.